2010
DOI: 10.1016/j.physbeh.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based differences in the behavioral and neuronal responses to food

Abstract: Sex-based differences in food intake related behaviors have been observed previously. The objective of this study was to examine sex-based differences in the behavioral and neuronal responses to food. 22 women and 21 men were studied. After 6 days of controlled eucaloric feeding, ad libitum energy intake (EI) was measured for three days. Appetite ratings using visual analog scales were obtained before and after each meal. Functional magnetic resonance imaging was performed in the overnight fasted state on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
122
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 52 publications
(53 reference statements)
19
122
5
1
Order By: Relevance
“…Interestingly though, in men the extent of deactivation in visual attention regions was greater, suggesting that they are less responsive to food cues. This is in line with others showing sex differences in visual-attention brain regions [50,62]. The greater activity in the visual cortices may be an important component in the cognitive process of the control of energy intake and of related behavior in women.…”
Section: Exercise and Neuronal Responsessupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly though, in men the extent of deactivation in visual attention regions was greater, suggesting that they are less responsive to food cues. This is in line with others showing sex differences in visual-attention brain regions [50,62]. The greater activity in the visual cortices may be an important component in the cognitive process of the control of energy intake and of related behavior in women.…”
Section: Exercise and Neuronal Responsessupporting
confidence: 92%
“…Several studies have evaluated neuronal responses to visual food cues at rest, showing changes in brain regions essential to the regulation of energy intake [48][49][50][51][52][53][54][55][56]. Killgore et al [51] observed significant activity in numerous food reward, inhibitory control, and visual brain regions (e.g., insula, amygdala, medial frontal gyrus, precuneus, etc.)…”
Section: Exercise and Neuronal Responsesmentioning
confidence: 99%
“…34 All these functions can be assigned to areas in the LPFC reaching from the rostral to the caudal to the pre-motor compartments. Evidence supporting the assumption that the DLPFC also has a crucial role in the cognitive control of eating behavior comes from a recent study by Cornier et al 35 Using fMRI, they found increased hemodynamic responses in the DLPFC of women to visually presented food after a eucaloric diet, suggesting increased automatic alertness and inhibitory effects owing to dieting. The correlations observed in our subjects suggest that individuals with high cognitive control over eating behavior (that is, high CRE values) show enhanced hemodynamic responses in the control-related prefrontal areas not only during the regulation of desire for food but, interestingly, also when admitting to it.…”
Section: Discussionmentioning
confidence: 81%
“…Men and women often have different social perceptions regarding the sensory properties of food, because women pay more attention to nutrition content than men (11) . Despite numerous studies focusing on gender-related differences in behavioural and neuronal responses to food (12)(13)(14) , little research has been published that compares specific sensory properties between genders with diet models of different ED.…”
Section: Energy Density Food Preference Gender Differencesmentioning
confidence: 99%
“…Men and women often have different social perceptions regarding the sensory properties of food, because women pay more attention to nutrition content than men (11) . Despite numerous studies focusing on gender-related differences in behavioural and neuronal responses to food (12)(13)(14) , little research has been published that compares specific sensory properties between genders with diet models of different ED.Given the close association of sensory properties and dietary ED (15) , and in light of previously studied relationships of age-related variations of fullness and satisfaction with particular energy-dense diet models (16) , in the current epidemiological study our aim was to examine gender-related † These authors contributed equally to this work. …”
mentioning
confidence: 99%